Prevention of Tetanus - Sisy Rizkia Putri (Global Health Science Group, 2020)
Tetanus is an acute disease characterized by muscle stiffness and spasm, due to the toxin produced by Clostiridium Tetani causing pain, usually in the lower jaw and neck. The method used in this writing is a review study. The purpose of the authors in conducting this literature study is to present, increase knowledge about prevention of tetanus. The main sources used are books and articles from literature searching on PubMed, google scholar, or others. Article searches are used with keywords such as tetanus, prevention, risk factors, clinical symptoms, vaccines. Articles were filtered with search terms from 2010-2020 and produced 1100 articles which were then selected 30 articles. Analysis using systematic study literature method is used for collection and evaluation of the intended learning focus. The results of this literature study indicate that prevention can be done with the tetanus vaccine. The discovery of this vaccine can reduce the incidence rate. Good wound handling can also be a powerful way to prevent tetanus.